Medical students’ knowledge of ultrasonography: effects of a simulation-based ultrasound training program - Eroglu, Oguz (Pan Afr Med J, 2018)
INTRODUCTION: The use of simulation devices in medical education is becoming more prevalent with each passing day. The present study aimed to teach medical students to perform ultrasonography via a simulation-based ultrasound training program. METHODS: The study was prospectively conducted on final year medical students who had not received previous ultrasound training and who came to the Emergency Department of the Kirikkale University Faculty of Medicine between July 2015 and July 2016. Ultrasound training was provided by two emergency department specialists who are qualified in this field. The training time was determined to be 20h (4h for theoretical lessons, 16h for hands-on). The students were evaluated by a theory test and practical application exam both before and after training. RESULTS: Obtained were compared using the paired sample t-test, and p < 0.05 was considered to be significant. Results: Ninety-six final year medical students were included. Their mean age was 24.1 ± 2.1 years. The mean test score obtained in the theoretical exam before training was 7.9 ± 2.2, while that after training was 17.1 ± 1.6 (p < 0.0001). The mean score obtained in the practical application exam before training was 1.1 ± 0.9 points and that after training was 10.9 ± 0.2 points (p < 0.0001). CONCLUSION: Medical students can learn to use an ultrasound device within a short period of time via simulation-based training programs. New studies must be conducted for the inclusion of ultrasound training programs in the medical education curriculum.